The role of OCT angiography in a study of retinal perfusion after endovitreal intervention due to rhegmatogenous retinal detachment - Rinat R. Fayzrakhmanov; Anna V. Sukhanova; Oleg A. Pavlovsky; Evgenia A. Larina (Клиническая практика, 2020)
OCT angiography is a non-invasive method of the qualitative and quantitative analysis of the retinal perfusion. After rhegmatogenous retinal detachment and vitrectomy with endotamponade, the retinal perfusion changes. Aim: To analyze the data from the clinical studies that evaluate the changes in the blood microcirculation of the retina and choroid and theireffect on the visual acuity by OCTA after vitrectomy with endotamponade due to rhegmatogenous retinal detachment. A literature search was conducted using PubMed, Cochrane Library, and Embase until April, 2020. The authors conclude that the specific changes in the retinal perfusion after vitrectomy due to regmatogenous retinal detachment using various types of tamponade may act as predictors of visual outcomes, and also may become a basis for determining the optimal time of the silicone oil tamponade resolution. Evaluation of these changes according to the data obtained using OCTA is promising and little-studied. Thus, additional clinical studies are required.